The Effect of Training and Work Environment on Employee Performance in the Fire Department - Ajeng Afifah Mustikasari; Ari Sulistyowati; Christophorus Indra Wahyu Putra; Tyna Yunita (IJESM Indonesian Journal of Economics and Strategic Management, 2023)
This study aims to determine whether there is an influence of Training and Work Environment on Employee Performance in the Fire Department. The sampling technique was carried out using a saturated sample technique obtained by 88 samples. The method used is quantitative method. This study used multiple linear regression analysis, and hypothesis test using t test and F test. The results of the study conducted in the t test (partial) training variable had an effect on performance with a sig value of 0.004 < 0.05 and a calculated t value of 6.173 t > table 1.988. The work environment variable did not have a significant effect on performance by obtaining a t count of 1.689 < t table 1.988 with a sig of 0.095 > 0.05. The results obtained from the F test (simultaneous) variables of training, work environment and performance affect simultaneously with the calculation results F calculated at 42.885 > 3.10 with a sig value of 0.000 < 0.05.